A comparative study of three different nucleic acid amplification techniques combined with microchip electrophoresis for HPV16 E6/E7 mRNA detection1. Issue 19 (7th October 2015) - Liu, Quanli; Lin, Xuexia; Lin, Luyao; Yi, Linglu; Li, Haifang; Lin, Jin-Ming
<x xml:space="preserve">Abstract</x> The development of a high-throughput and automatic system by combining gene amplification with MCE for HPV16 E6/E7 mRNA screening is reported.